Az Északnyugat-Dunántúl területfejlesztési stratégiája (tervezet) - Rechnitzer, János; Lados, Mihály (Tér és Társadalom, 1997)
The study introduces the development strategy of a region comprising four counties. North-West Transdanubia is an active area of Hungarian modernisation, a region where the counties show significant differences in the levei of their development. Using the method of strategy building, the essay considers the strengths and weaknesses of the region and looks at the possibilities and threats of development. The SWOT analysis reveals three scenarios for the future of the region. The first prospect of the future is a projection of the present situation, the second one considers a more moderate economic growth while the third one suggests a dynamic development. The authors state the mission of the region based on the second scenario. The mission of the regional developments is to promote the already started economic transitions and provide a suitable environment for them. The objectives of the development and their programme versions are also included in the study. Finally it defines the regions where intervention is necessary, pointing at their particular features and the development possibilities. The development strategy was an experiment to find what principles and methods can be the hasis on which the future prospects of a territory – which is not yet a functional region – can be worked out.